Evaluation of the Effect of Social Care Collaboration on the Psychological State of the Parents of Children with Leukemia - Cui Wang; Bo Zhao; Ping Fang (SAGE Open, 2024)
The quality of life of children with leukemia can be affected by their parents’ emotional stress. We examined the effects of social care collaboration on the psychological states of parents of children with leukemia. This was a prospective, single-center, randomized study. The parents of children diagnosed with leukemia between January 1 and December 31, 2021, were divided randomly into experimental and control groups, in which the health education model and psychological counselling by medical social workers paired with online health education by nurses were used, respectively. Questionnaire surveys were used to evaluate their psychological state. Data were analyzed using t -test and linear regressions. Varying degrees of anxiety and depression were present in 94% of the participants. Anxiety and depression scores were significantly different between the groups, as indicated by the SAS ( p  = .002), SDS ( p  = .016), and SCL-90 ( p  = .015) scales. Income level was related to the degree of anxiety ( p  = .047). Although anxiety and depression scores of both groups declined with time, the trend showed no significant difference (anxiety: p  = .957; depression: p  = .776). Social care collaboration was beneficial in relieving negative emotions in parents of children with leukemia.